Geografia dos transportes: trajetos e conflitos nos percursos fluviais da Amazônia Paraense: um estudo sobre acidentes em embarcações - Bastos, Maria Martins da Rocha Diniz (2006)
The transport is a essential factor on territory s development and ordination it can be on local or regional level, because it is responsible for people circulation and load, performing strategically part for special-relations and economics, developing with on height ore low intensity on geography places consequences. On this view, the fluvial transport came, and has acquiring of progressive effectual mobility, safety and practicable. Between the existent motility economics, the fluvial, is the cheapest and can attend the needs of loads and people transportation on a integral way, in case it has economic, adjust and structure to its traffic. Nevertheless, the history of the country s occupation on has determinate that the same was not priority and today, even having higher coast in every ways, the road transportation prevail as modality that attract praticaly all public invest, resolting the most used on this way, loses the opportunity to promote the circulation of people and load on a higher economic way, safer and more democratic. On Amazônia region, this problematic is considerly intense once that the same is composed on the magor part of it s territorial space of navigate rivers of big volume of water. The fluvial transportation is used on a intense way by it s population on commercial and domestic ambit. Even before this reality, the fluvial transportation it s not priority as one of the mains sources of socialeconomics invest, once that those are part of majority amazon s daily. This master teses has the purpose to now, study and comprehend the fluvial transport of amazonia region, on metropolitan area. Capital of Pará, Belém as were as others municipality on this locals, the navigation is used on intense ways and very important to it s regional and national. For to understand this reality, this ressurch propose to know the inter fluvial way, and with that the accident accord on fluvial travel with small boats, specially the scalpelment through axle- motor boats. The kind of accident, although tragic, is comun on amazon s region, and mainly with depend intimately of this modality to exercise practically all daily activities according with given quantity and study development, makes important to show the aspect that important to show the aspect that characterize the fact, turning evident reality performed and it s consequences, through out the conclusions and opening perspective for more proper situation.